English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Perform the indicated operation and write your answer in standard form:
x^2- 13x + 36= 0

2007-01-11 09:41:57 · 6 answers · asked by melanie m 2 in Science & Mathematics Mathematics

6 answers

Simplifying
x2 + -13x + 36 = 0

Reorder the terms:
36 + -13x + x2 = 0

Solving
36 + -13x + x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(4 + -1x)(9 + -1x) = 0

Subproblem 1Set the factor '(4 + -1x)' equal to zero and attempt to solve:

Simplifying
4 + -1x = 0

Solving
4 + -1x = 0

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -1x = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -1x = 0 + -4
-1x = 0 + -4

Combine like terms: 0 + -4 = -4
-1x = -4

Divide each side by '-1'.
x = 4

Simplifying
x = 4
Subproblem 2Set the factor '(9 + -1x)' equal to zero and attempt to solve:

Simplifying
9 + -1x = 0

Solving
9 + -1x = 0

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -1x = 0 + -9

Combine like terms: 9 + -9 = 0
0 + -1x = 0 + -9
-1x = 0 + -9

Combine like terms: 0 + -9 = -9
-1x = -9

Divide each side by '-1'.
x = 9

Simplifying
x = 9Solutionx = {4, 9}

I Got all of this at algebrahelp.com i get a lot of my math answers from there-- use their calculators

2007-01-11 09:50:36 · answer #1 · answered by secret_spencer 1 · 3 0

I assume you need to solve.
x^2 - 13x + 36 = 0
Factor. What factors of 36 add up to -13? -9 and -4 do.
(x-9)(x-4) = 0
x - 9 = 0 or x - 4 = 0
x = 9 or x = 4

2007-01-11 09:44:32 · answer #2 · answered by MsMath 7 · 2 2

The answer is both x=9 and x=4. And yes, the factor was correct (x-9)(x-4).

2007-01-11 09:52:42 · answer #3 · answered by trent_tech 1 · 1 0

Here it is factored:
(x-9)(x-4)
which would make:
x=4 and x=9

2007-01-11 09:45:37 · answer #4 · answered by Bre 2 · 1 0

Is this factoring?
if it is that's the answer
(x-9)(x-4)

2007-01-11 09:46:59 · answer #5 · answered by B9O9R9I9C9U9A 3 · 1 0

OMG!! my class is doing this stuff!!! algebra right?
well im pretty sure the answer is

(x - 9)(x - 4)
x^2-9x-4x + 36 = 0

9,4 - this should be the ANSWER!!!!

2007-01-11 09:48:36 · answer #6 · answered by England France 2 · 0 1

fedest.com, questions and answers